An Analysis of Syllabus and Materials Provided By the English Lecturer at a Private Higher Education of Informatics in Bandung - Marjito Marjito (Jurnal Computech & Bisnis (e-Journal), 2015)
This study was aimed to find out whether the syllabus and material provided by the English lecturer of informatics department  match with both the concept of English for Specific Purpose (ESP) and students’ needs. This study was conducted in three departments (Manajemen Informatika, Teknik Informatika, and Komputerisasi Akuntansi) of Higher Education of Computer Science (HECS) and involved six students from various level of English proficiency (low, mid, and high achiever). This study used a qualitative approach, particularly case  study. The data for the study were collected through interviews, syllabus, and materials. syllabus and material were analyzed by using the available theories, like Hutchinson and Water (1087), Dudely-Evans and St. John (1998), and other theories in chapter 2. Then, the findings data  from interviews were matched to the data from syllabus and material whether syllabus and material were relevance to the need of students’ or not. This study reveals that the learners’ need are generally mismatched to syllabus and material provided by the lecturer, meanwhile type of syllabus used in the syllabus is a combination of structural syllabus, functional syllabus, and organizational syllabus. Moreover, most of the materials were categorized as general English. From the findings, it was clear that the lecturer didn’t fully design either syllabus or materials based on ESP as students’ need.  The lecturer, therefore,  should  conduct students’ need analysis before designing syllabus and material (students centered). Keywords: english for specific purpose; students’ needs